You are on page 1of 21

Short Review of Basic Mathematics

Tomas Co

March 31, 2011


2 c 2011 Tomas Co, all rights reserved
°
Contents

1 Review of Functions 5
1.1 Mathematical Identities . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 5
1.2 Drills . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 7
1.3 Answers to Drills . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 8

2 Review of ODE Solutions 11


2.1 First Order Differential Equations . . . . . . . . . . . . . . . . . . . . . . . . 11
2.2 High Order Linear ODEs with Constant Coefficients . . . . . . . . . . . . . . 12
2.3 Drills . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 14
2.4 Answers to Drills . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 15

3 Review of Matrix Operations 17


3.1 Basic Operations . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 17
3.2 Determinants . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 18
3.3 Matrix Inverse . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 19
3.4 Drills . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 20
3.5 Answer to Drills . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 21

3
4 c 2011 Tomas Co, all rights reserved
°
Chapter 1

Review of Functions

1.1 Mathematical Identities


1
1. e−b =
eb

2. ea+b = ea eb

3. eln(x) = x

4. ln (ex ) = x

5. ln (ab) = ln(a) + ln(b)

³a´
6. ln = ln(a) − ln(b)
b

7. ln (xa ) = a ln(x)

ln(x) ln(x)
8. log (x) = ≈
ln(10) 2.303

9. cos (a + b) = cos(a) cos(b) − sin(a) sin(b)

10. sin (a + b) = cos(a) sin(b) + sin(a) cos(b)

5
6 c 2011 Tomas Co, all rights reserved
°

11. cos2 (x) + sin2 (x) = 1

12. cos2 (x) − sin2 (x) = cos (2x)

13. 2 sin(x) cos(x) = sin (2x)



2 −b ± b2 − 4ac
14. ax + bx + c = 0 → x=
2a

15. (a + b) (a − b) = a2 − b2

16. (a + b)2 = a2 + 2ab + b2


µ ¶
n n n−1 n!
17. (a + b) = a + na b + ... + an−k bk + . . . + bn
(n − k)!k!
. where n! = (n)(n − 1) · · · (3)(2)(1) and 0! = 1


Define the imaginary number: i = −1

18. (a + ib) (a − ib) = a2 + b2

19. eit = cos(t) + i sin(t)

20. e−it = cos(t) − i sin(t)

eit + e−it
21. cos(t) =
2
eit − e−it
22. sin(t) =
2i

d a
23. t = a ta−1
dt
d t
24. a = at ln(a)
dt
d at
25. e = aeat
dt
c 2011 Tomas Co, all rights reserved
° 7

d 1
26. ln (at) =
dt t
d
27. sin(t) = cos(t)
dt
d
28. cos(t) = − sin (t)
dt
d ³ ´ df dg
29. Derivative of Sums: f (t) + g(t) = +
dt dt dt
µ ¶ µ ¶
d ³ ´ df dg
30. Derivative of Products: f (t)g(t) = g(t) + f (t)
dt dt dt
µ ¶ µ µ ¶¶
d f (t) 1 dg df
31. Derivative of Fractions: = 2 f (t) − g(t)
dt g(t) f (t) dt dt
d ³ ´ df du
32. Chain Rule: f u(t) =
dt du dt
Z b³ ´ Z b Z b
33. p f (t) + q g(t) dt = p f (t)dt + q g(t)dt
a a a
Z b Z c Z c
34. f (t)dt + f (t)dt = f (t)dt
a b a
Z v(b) ³ ´ Z u(b)
35. Integration by parts: u dv = u(b)v(b) − u(a)v(a) − v du
v(a) u(a)

1.2 Drills
d ¡ 1+3t ¢
1. Find 2e − t2 + 10
dt
d ³ 2
´
2. Find ln (at) et+it
dt

3. Find the roots of : 3x2 + 2x = 4

4. Find the solution of : 2 log (x + 3) = log (x + 15)

5. Expand (x + y)4 into a polynomial in x and y


8 c 2011 Tomas Co, all rights reserved
°

6. Prove the following identity:


³ ´
p+iq p−iq p
(a + ib) e + (a − ib) e =e 2a cos(q) − 2b sin(q)

Z 10 ³ ´
2 −2t
7. Find 2+t e dt
0

8. Let r be a function of t. Show that the following is true:

d ¡ ¢ dr
2πr2 + 5r = (4πr + 5)
dt dt

9. Find k and φ such that: 2 cos (3t) + 4 sin (3t) = k sin (3t + φ)

Z 2

 t if t ≤ 1
10. Find tf (t)dt, where f (t) =
0 
 2−t if t > 1

1.3 Answers to Drills


1. 6e1+3t − 2t
µ ¶
1 2
2. + ln (at) (1 + 2it) et+it
t
√ √
1 + 13 1 − 13
3. x1 = , x2 =
3 3

4. x=1

5. x4 + 4x3 y + 6x2 y 2 + 4xy 3 + y 4

6.
³
(a + ib) ep+iq + (a − ib) ep−iq = ep (a + ib) (cos(q) + i sin(q))
´
(a − ib) (cos(q) − i sin(q))
³ ´
= ep 2a cos(q) − 2b sin(q)
c 2011 Tomas Co, all rights reserved
° 9

81 221 −20
7. − e
4 4
8. Hint: use chain rule

9.

2 cos(3t) + 4 sin(3t) = k sin(3t + φ)


= (k sin(φ)) cos(3t) + (k cos(φ)) sin(3t)

Comparing coefficients on both sides



k cos(φ) = 4 k = 20 ¡ ¢

k sin(φ) = 2 φ = Atan 12

Z 1 Z 2
2
10. t dt + (2 − t)tdt = 1
0 1
10 c 2011 Tomas Co, all rights reserved
°
Chapter 2

Review of ODE Solutions

2.1 First Order Differential Equations


1. Separable Type
dx
• Form : = f (t)g(x) subject to x(0) = xo
dt
Z x Z t
1
• Solution: dx = f (t)dt
xo g(x) 0
• Example:
dx x
=5 x(0) = 2
dt 1+t
5
then f (t) = and g(x) = x,
1+t
Z x Z t
1 5
dx = dt
x0 x 0 1+t
³ ´
ln (x) − ln (x0 ) = 5 ln (1 + t) − ln(1)
µ ¶
x
ln = 5 ln (1 + t)
x0
x
= (1 + t)5
x0
x = x0 (1 + t)5

2. Linear First Order


dx
• Form : + p(t)x = q(t) subject to x(0) = xo
dt

11
12 c 2011 Tomas Co, all rights reserved
°

µZ ¶
• Solution: Let φ = exp p(t)dt be an integrating factor, then
µ Z t ¶
1
x= x0 + q(τ )φ(τ )dτ
φ(t) 0

• Example:
dx
+ 2tx = 4t x(0) = x0
dt
then p(t) = 2t and q(t) = 4t,
R 2
2tdt
φ(t) = e = et
and
µ Z t ¶
−t2 τ2
x = e x0 + 4τ e dτ
0
2
³ 2
´
= e−t x0 − 2 + 2et
2
= 2 + (x0 − 2) e−t

2.2 High Order Linear ODEs with Constant Coeffi-


cients
dn x dx
• Form : an + · · · + a1 + a0 x = q(t)
dtn dt
dn−1 x
subject to x(0) = xo,0 , . . . , (0) = xo,n−1
dtn−1

• Solution: x(t) = xc (t) + xp (t)

where

– xc is the complementary solution which solves

dn xc dxc
an n
+ · · · + a1 + a0 xc = 0
dt dt

– xp is the particular solution which solves

dn xp dxp
an n
+ · · · + a1 + a0 xp = q(t)
dt dt
c 2011 Tomas Co, all rights reserved
° 13

• Example: Second Order

d2 x dx
a2 + a 1 + a0 x = q(t)
dt2 dt

Step 1: Find xc :

1. Get the characteristic polynomial,

a2 s2 + a1 s + a0 = 0

2. Solve for the roots, also known as eigenvalues,


p p
−a1 + a21 − 4a2 a0 −a1 − a21 − 4a1 a0
r1 = r2 =
2a2 2a2
3. Form the complementary solution to be

xc = C1 y1 (t) + C2 y2 (t)

where

y1 (t) = er1 t


 er2 t if r1 6= r2
y2 (t) =

 ter1 t if r1 = r2

where C1 and C2 are constants, evaluated later to fit the initial conditions

Step 2: Find xp :

Method : Variation of Parameters


dy2 dy1
1. Evaluate the Wronskian: W (t) = y1 − y2
dt dt
2. Calculate u1 and u2 :
Z Z
y2 (t)q(t) y1 (t)q(t)
u1 (t) = − dt u2 (t) = dt
a2 W (t) a2 W (t)
3. Form the particular solution: xp (t) = u1 (t)y1 (t) + u2 (t)y2 (t)

Step 3: Use initial conditions to determine the values of C1 and C2 .


14 c 2011 Tomas Co, all rights reserved
°

• Numerical Example:

d2 x dx dx
+ − 6x = e−t sin (2t) subject to x(0) = 1, (0) = 0
dt2 dt dt
– Step 1: complementary solution

s2 + s − 6 = 0 → r1 = −3 ; r2 = 2 → y1 = e−3t ; y2 = e2t

xc = C1 e−3t + C2 e2t
– Step 2: particular solution

W (t) = 5e−t
1 2t ³ ´
u1 (t) = e cos(2t) − sin(2t)
20
1 −3t ³ ´
u2 (t) = e −2 cos(2t) − 3 sin(2t)
65
1 −t ³ ´
→ xp (t) = e cos(2t) − 5 sin(2t)
52
– Step 3: determine integration constant

x = xc + x p
1 −t ³ ´
= C1 e−3t + C2 e2t + e cos(2t) − 5 sin(2t)
52
1
x(0) = 0 = C1 + C2 +
52
dx 11
(0) = 0 = −3C1 + 2C2 −
dt 52

7 41
→ C1 = C2 =
20 65
7 41 1 ³ ´
Solution: x(t) = e−3t + e2t + e−t cos(2t) − 5 sin(2t)
20 65 52

2.3 Drills
Solve the following differential equations

dx
1. = e−t (x + 2) subject to x(0) = 1
dt
c 2011 Tomas Co, all rights reserved
° 15

dx
2. + (1 + t) x = sin(2t) subject to x(0) = 1
dt
d ¡ 2t ¢
3. e x = e−t subject to x(0) = 2
dt
d2 x dx dx
4. + 4 + 4x = 3 + e−t sin (t) subject to x(0) = 2 and (0) = 0
dt2 dt dt
d2 x dx dx
5. 2
− e−2t = −5 − 6x subject to x(0) = 0 and (0) = 0
dt dt dt

2.4 Answers to Drills


³ ´
1. x(t) = exp 1 + ln(3) − e−t − 2
µ Z t ¶ µ ¶
1 t2 + 2t
2. x(t) = 1+ φ(τ ) sin(2τ )dτ where φ(t) = exp
φ(t) 0 2
3 − e−t
3. x(t) =
e2t
µ ¶
3 7 −2t 1 −t
4. x(t) = + 3t + e − e cos(t)
4 4 2

5. x(t) = e−3t + (t − 1) e−2t


16 c 2011 Tomas Co, all rights reserved
°
Chapter 3

Review of Matrix Operations

3.1 Basic Operations


1. Addition:
     
a11 · · · a1n b11 · · · b1n (a11 + b11 ) · · · (a1n + b1n )
 .. . .. .   .
..  +  .. . .. .  
..  =  .. .. .. 
 . . . . 
am1 · · · amn bm1 · · · bmn (am1 + bm1 ) · · · (amn + bmn )
µ ¶ µ ¶ µ ¶
1 0 −1 −1 2 2 0 2 1
Example: + =
2 1 3 2 2 0 4 3 3
2. Scalar Product:
   
a11 · · · a1n γa11 · · · γa1n
 .. ... ..   .. ... .. 
γ . . = . . 
am1 · · · amn γam1 · · · γamn
   
2 4 6 12
Example: 3 2 1 = 6 3 
1 −1 3 −3
3. Matrix Product:
    
a11 · · · a1n b11 · · · b1p c11 · · · c1p
 .. .. ..   .. . . .   . .. . 
 . . .  . . ..  =  .. . .. 
am1 · · · amn bn1 · · · bnp cm1 · · · cmp
where,
n
X
cij = aik bkj i = 1, . . . , m j = 1, . . . , p
k=1

17
18 c 2011 Tomas Co, all rights reserved
°

Example:  
µ ¶ −1 2 µ ¶ µ ¶
1 1 −1  (−1 + 2 − 1) (2 + 2 + 0) 0 4
2 2 = =
2 2 3 (−2 + 4 + 3) (4 + 4 + 0) 5 8
1 0
4. Transpose:
 T  
a11 · · · a1n a11 · · · a1m
 .. ... ..   . .. 
 . .  =  .. . . . . 
am1 · · · amn an1 · · · anm
 T
1 2 µ ¶
Example:  3 4  = 1 3 5
2 4 6
5 6

3.2 Determinants
Notation: det(A) = |A|

1. 2 × 2 Matrices: ¯µ ¶¯
¯ a11 a12 ¯
¯ ¯
¯ a21 a22 ¯ = a11 a22 − a12 a21
¯µ ¶¯
¯ 1 2 ¯
Example: ¯ ¯
¯ 3 2 ¯ = 1 · 2 − 2 · 3 = −4

2. n × n Matrices:
Method 1: row expansion
(a) Given matrix A, choose any row, say row i.
(b) Let Aij↓ be matrix A with row i and column j removed.
(c) The determinant can be determined recursively by
Xn ¯ ¯
¯ ¯
|A| = (−1)i+j ¯Aij↓ ¯
j=1

Example: Expand along row 2,


¯ ¯
¯ 1 2 −1 ¯ ¯µ ¶¯ ¯µ ¶¯
¯ ¯ ¯ 2 −1 ¯ ¯ 1 −1 ¯¯
¯ 3 2  ¯
0 ¯ = 3 · (−1) ¯ 2+1 ¯ ¯ 2+2 ¯
+ 2 · (−1) ¯
¯ 1 1 ¯ −1 1 ¯
¯ −1 1 1 ¯
¯µ ¶¯
¯
2+3 ¯ 1 2 ¯¯
+ 0 · (−1) ¯
−1 1 ¯
= −9
c 2011 Tomas Co, all rights reserved
° 19

Method 2: column expansion

(a) Given matrix A, choose any column, say column j.


(b) Let Aij↓ be matrix A with row i and column j removed.
(c) The determinant can be recursively determined by
n
X ¯ ¯
¯ ¯
|A| = (−1)i+j ¯Aij↓ ¯
i=1

Example: Expand along column 2,


¯ ¯
¯ 1 2 −1 ¯ ¯µ ¶¯ ¯µ ¶¯
¯ ¯ ¯ 3 0 ¯ ¯ 1 −1 ¯
¯ 3 2 0 ¯ = 2 · (−1) ¯ 1+2 ¯ + 2 · (−1) ¯
2+2 ¯
¯ ¯ ¯ −1 1 ¯ ¯ −1 1 ¯
¯ −1 1 1 ¯
¯µ ¶¯
¯ 1 −1 ¯
3+2 ¯
+ 1 · (−1) ¯ ¯
3 0 ¯
= −9

3.3 Matrix Inverse


1. 2 × 2 Matrices:
µ ¶−1 µ ¶
a11 a12 1 a22 −a12
=
a21 a22 |A| −a21 a11
Example:
µ ¶−1 µ ¶ µ ¶
1 2 1 2 −2 −1/2 1/2
= =
3 2 1 · 2 − 2 · 3 −3 1 3/4 −1/4

µ ¶µ ¶−1 µ ¶
−1 −1/2 1/2 1 2 1 0
Checking: A A= =
3/4 −1/4 3 2 0 1
2. n × n Matrices:

(a) Given matrix A, let Aij↓ be matrix A with row i and column j removed.
(b) Build a new matrix B,  
b11 · · · b1n
 
B =  ... . . . ... 
bn1 · · · bnn
where bij = (−1)i+j |Aij↓ |.
20 c 2011 Tomas Co, all rights reserved
°

(c) The inverse of A is given by


1 T
A−1 = B
|A|

1 2 3
Example: Let A =  3 2 0  then
0 1 −2
¯µ ¶¯ ¯µ ¶¯ ¯µ ¶¯
¯ 2 0 ¯ ¯ 3 0 ¯ ¯ 3 2 ¯
b11 = ¯ ¯ ¯ ¯ ¯ ¯
¯ 1 −2 ¯ ; b12 = − ¯ 0 −2 ¯ ; b13 = ¯ 0 1 ¯
¯µ ¶¯ ¯µ ¶¯ ¯µ ¶¯
¯ 2 3 ¯ ¯ 1 3 ¯ ¯ 1 2 ¯
b21 = − ¯¯ ¯ ; b22 = ¯ ¯ ¯ ¯
¯ 0 −2 ¯ ; b23 = − ¯ 0 1 ¯
1 −2 ¯
¯µ ¶¯ ¯µ ¶¯ ¯µ ¶¯
¯ 2 3 ¯ ¯ 1 3 ¯¯ ¯ 1 2 ¯
b31 = ¯ ¯ ; b32 = − ¯ ; b33 = ¯ ¯
¯ 2 0 ¯ ¯ 3 0 ¯ ¯ 3 2 ¯
 
−4 6 3
B=  7 −2 −1 
−6 9 −4
Expanding along row 3,
¯µ ¶¯ ¯µ ¶¯
¯ 1 3 ¯ ¯ 1 2 ¯
|A| = 0 + 1 · (−1)3+2 ¯
·¯ ¯ 3+3 ¯
− 2 · (−1) ¯ ¯ = 17
3 0 ¯ 3 2 ¯
Thus, the inverse is given by
 T  
−4 6 3 −4/17 7/17 −6/17
1 
A−1 = 7 −2 −1  =  6/17 −2/17 9/17 
17
−6 9 −4 3/17 −1/17 −4/17
Checking:
    
−4/17 7/17 −6/17 1 2 3 1 0 0
A−1 A =  6/17 −2/17 9/17   3 2 0 = 0 1 0 
3/17 −1/17 −4/17 0 1 −2 0 0 1

3.4 Drills
   
1 2 1 −1 1 µ ¶ µ ¶
2 1 1 0
Let A =  3 4 , B= 3 2 0 , C= and I2 =
3 2 0 1
1 1 1 2 2
and let s be a scalar variable.
Evaluate the following:
c 2011 Tomas Co, all rights reserved
° 21

1. AAT − B

2. ACAT

3. B −1
³ ´−1
4. sI2 − C

5. BC

3.5 Answer to Drills


   
5 11 3 4 12 2
1. AAT =  11 25 7  → AAT − B =  8 23 7 
3 7 2 2 5 0
 
18 44 13
2. ACAT =  40 98 29 
11 27 8
 
4/14 4/14 −1/14
3. B −1 =  −6/14 1/14 3/14 
4/14 −3/14 5/14
µ ¶
−1 1 s−2 1
4. (sI2 − C) = 2
s − 4s + 1 3 s−2
5. Not applicable! Sizes of B and C are not conformable for the product BC.